ON THE STATE-OPTIMIZATION APPROACH TO SYSTEM PROBLEMS: CLOSED-LOOP THINKING SOLUTIONS - Anh, Nguyen Thuy; Anh, Nguyen Le (Vietnam Journal of Science and Technology, 2012)
State-optimization approach has been proposed to treating various different system problems in optimal projection equations (OPEQ). While the OPEQ for problems of open-loop thinking is found consisting of two modified Lyapunov equations, excepting the rank conditions whereas required in system identification and its related robust problems, the one for closed-loop thinking consists of two modified either Reccatti or Lyapunov equations, excepting conditions for compensating system happened to be in a problem like that of order reduction for controller. Apart from addditonally constrained-conditions and simplicity in the solution form have been obtainable for each problem, it has been found the system identification problem switching over to computing the solution of OPEQ and the physical nature of medeled states possibly retaining in optimal order reduction problem.